Integrasi Higher Order Thinking Skill (HOTS) Dan Creative Problem Solving Pada Pembelajaran Sains di MI/SD - Akhmad (IAI Al Khoziny Buduran Sidoarjo, 2021)
Teachers have an important role in creating quality learning processes and outcomes. Quality learning is created when teachers are able to integrate in their fields, especially pedagogic competencies that are directly related to the learning process, science learning in MI/SD is important to note how the integration between the Higher Order Thinking Skills (HOTS) learning model and the Creative Problem Solving Model in learning is. Science learning in MI/SD is. The purpose of this journal study is to find out the integration between Higher Order Thinking Skills (HOTS) and the Creative Problem Solving Model in Learning in MI/SD. This research is a descriptive qualitative research based on literature or literature review. The results showed that the integration between Higher Order Thinking Skills (HOTS) and the Creative Problem Solving Model in MI/SD learning has been studied in learning that includes Higher Order Thinking Skills (HOTS) and Creative Problem Solving (CPS) models. Existing practice questions, materials and learning designs contain all the integration between Higher Order Thinking Skills (HOTS) and Creative Problem Solving Models in Learning in MI/SD.